Multilayer composite lithium ion conductor film, method for manufacturing the same, and solid-state lithium battery
Patent Information
- Application Number
- CN202311195779.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2026-09-22
- Estimated Expiration
- 2043-09-15
AI Technical Summary
[0010]本发明的目的是为了克服现有的单层锂离子导体膜的电化学稳定窗口有限,无法与高比能量电极材料相匹配以实现良好微观和宏观接触,电解质或电极组分易存在副反应,以及湿度稳定性差的问题
[0023]1、本发明提供的多层复合锂离子导体膜包括依次层叠设置的第一稳定膜层、反钙钛矿电解质膜层和第二稳定膜层;所述第一稳定膜层含有石榴石结构锂离子导体、第一粘结剂和含氟锂盐;所述反钙钛矿电解质膜层含有反钙钛矿结构锂离子导体和第二粘结剂;所述第二稳定膜层含有石榴石结构锂离子导体、第三粘结剂和含氟锂盐;其中,所述反钙钛矿结构锂离子导体的平均粒径大于石榴石结构锂离子导体的平均粒径;所述第一稳定膜层中含氟锂盐的含量高于所述第二稳定膜层中含氟锂盐的含量。
Smart Images

Figure CN117039116B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid-state lithium batteries, specifically to multilayer composite lithium-ion conductor films, their preparation methods, and solid-state lithium batteries. Background Technology
[0002] Traditional liquid lithium-ion batteries have limited energy density and pose safety risks. Solid-state batteries, on the other hand, boast high theoretical energy density, a wide temperature range, and good safety, making them a promising energy storage technology. High-safety, high-energy-density all-solid-state batteries are an inevitable trend in technological development. In recent years, the power battery industry has experienced rapid growth, leading to an imbalance between supply and demand, accompanied by shortages of power battery materials and significant price premiums. For new energy vehicles to continue competing with traditional gasoline vehicles in the market, they must achieve comparable levels in terms of range and cost, making the development of new power battery systems urgent. Solid-state batteries using non-flammable inorganic solid electrolytes are considered to fundamentally solve the safety issues of new energy vehicles and have become a key development direction in the power battery field. Solid-state batteries offer advantages in high energy density and high safety. Selecting suitable solid electrolytes and high-specific-capacity positive and negative electrode materials is crucial for achieving high-energy-density all-solid-state batteries. Developing solid electrolytes with high ionic conductivity, high electrochemical stability, and low cost has become one of the main research directions for developing novel all-solid-state batteries (ASSLB).
[0003] Currently, very few known solid-state electrolytes possess ionic conductivity comparable to that of typical liquid electrolytes. Solid-state electrolytes exhibiting relatively high ionic conductivity at room temperature include Li. 10 GeP2S 12 Li3OCl, Li7P3S 11 and Li 9.6 P3S 12 Many studies have been conducted to understand the physical properties and diffusion mechanisms of ions in these solid electrolytes.
[0004] Anti-perovskite materials are a particularly promising type of solid electrolyte because of their high ionic conductivity (10⁻⁶). -4 -10 -3Advantages include low S / cm (at room temperature), low activation energy (0.26 eV), low electronic conductivity, and wide electrochemical window. Typical anti-perovskite electrolytes, such as Li3OCl and Na3OBr, have electrochemical windows of approximately 0-3 V and 0-2 V, respectively. Therefore, these proton-free anti-perovskite electrolytes are thermodynamically stable with Li and Na metal anodes. However, for metastable anti-perovskite structures, perturbations from various influencing factors during the preparation and synthesis process will cause changes in the crystal structure of the final product. Materials with cubic or orthorhombic phases have lower lithium migration barriers. To prepare pure-phase materials with a single structural phase, the crystal structure of the material can be induced and controlled by compositional design of the anti-perovskite electrolyte, but the structure-activity relationship is not clear. In addition, the synthesis methods of inorganic electrolytes in the Li3OCl system mainly include hydrothermal methods and high-pressure solid-state methods, which have relatively harsh synthesis equipment and process conditions, resulting in poor humidity stability of the synthesized materials, and poor controllability of material morphology and electrochemical performance.
[0005] The tolerance factor (t), widely used to measure the stability of perovskites, was proposed by Goldschmidt in 1926 to predict the structural stability of perovskite structures. The stability of the target material can be estimated by simply calculating the radii of the cations and anions. The tolerance factor for stable perovskites typically ranges from 0.77 to 1.10. However, there are relatively few studies on its application in controlling the crystal structure of materials.
[0006] Currently, the energy density of most all-solid-state lithium batteries is far below expectations, largely due to the high thickness and weight of the electrolyte layer. Currently, it is necessary to press rigid inorganic solid electrolyte powder into sheets ranging in thickness from hundreds of micrometers to -1 mm to prevent the solid electrolyte layer from cracking. A thin solid electrolyte layer is crucial for assembling high-energy-density batteries. To achieve high energy and power densities, a layer with a thickness greater than 10 is typically required. -4 Solid-state electrolyte membranes with high ionic conductivity (micrometer scale) of S / cm are desired. However, current methods for producing such membranes present significant challenges. For example, vacuum radio frequency sputtering is prohibitively expensive, and methods such as atomic layer deposition (ALD), pulsed layer deposition (PLD), and chemical vapor deposition (CVD) are more time-consuming and have poor scalability compared to roll-to-roll processes. Developing inorganic solid-state electrolyte membranes is even more challenging than developing flexible polymer electrolytes due to their poor mechanical flexibility, poor air / humidity stability, and susceptibility to chemical side reactions with polar solvents and polymer binders.
[0007] To overcome these challenges, various feasible methods have been developed, including slurry coating, solution wetting, and dry film technology.
[0008] All-solid-state thin-film lithium batteries, which employ solid electrolyte / solid-state composite electrode films and have a thickness in the micrometer range, have advantages such as high safety, long lifespan, and high integration.
[0009] However, the low energy density of thin-film lithium batteries is the main bottleneck limiting their widespread application, and the currently developed battery material systems are relatively limited (mostly LiCoO2 / LiPON / Li systems). If novel electrode and electrolyte materials used in traditional lithium-ion batteries can be applied to thin-film lithium batteries, it is hoped that device performance can be improved from the fundamental material perspective to meet practical needs. Summary of the Invention
[0010] The purpose of this invention is to overcome the problems of existing single-layer lithium-ion conductor films having a limited electrochemical stability window, being unable to match high specific energy electrode materials to achieve good microscopic and macroscopic contact, being prone to side reactions in electrolytes or electrode components, and having poor humidity stability.
[0011] To achieve the above objectives, the first aspect of the present invention provides a multilayer composite lithium-ion conductor film, wherein the multilayer composite lithium-ion conductor film comprises a first stabilizing film layer, an anti-perovskite electrolyte film layer and a second stabilizing film layer stacked sequentially.
[0012] The first stable film layer contains a garnet-structured lithium-ion conductor, a first binder, and a fluorine-containing lithium salt;
[0013] The anti-perovskite electrolyte membrane contains an anti-perovskite structure lithium-ion conductor and a second binder.
[0014] The second stabilizing film contains a garnet-structured lithium-ion conductor, a third binder, and a fluorine-containing lithium salt;
[0015] The average particle size of the anti-perovskite lithium-ion conductor is greater than that of the garnet lithium-ion conductor; the content of fluorinated lithium salt in the first stable film layer is higher than that in the second stable film layer.
[0016] A second aspect of the present invention provides a method for preparing a multilayer composite lithium-ion conductor film as described in the first aspect, the method comprising the following steps:
[0017] (1) A garnet-structured lithium-ion conductor, a first binder and a fluorine-containing lithium salt are mixed and subjected to fiberization treatment to obtain a first stable film precursor;
[0018] (2) The anti-perovskite lithium-ion conductor and the second binder are mixed and subjected to fiberization treatment to obtain an anti-perovskite electrolyte membrane precursor.
[0019] (3) Garnet-structured lithium-ion conductor, third binder and fluorine-containing lithium salt are mixed and subjected to fiberization treatment to obtain second stable film precursor;
[0020] (4) The first stabilizing membrane precursor, the anti-perovskite electrolyte membrane precursor and the second stabilizing membrane precursor are sequentially combined.
[0021] A third aspect of the present invention provides a solid-state lithium battery, the solid-state lithium battery comprising a positive electrode, a negative electrode and a multilayer composite lithium-ion conductor film as described in the first aspect, wherein the positive electrode is located on one side of the first stabilizing film layer and the negative electrode is located on one side of the second stabilizing film layer.
[0022] Through the above technical solution, the present invention has the following advantages:
[0023] 1. The multilayer composite lithium-ion conductor membrane provided by the present invention comprises a first stable film layer, an anti-perovskite electrolyte film layer, and a second stable film layer stacked sequentially; the first stable film layer contains a garnet-structured lithium-ion conductor, a first binder, and a fluorinated lithium salt; the anti-perovskite electrolyte film layer contains an anti-perovskite-structured lithium-ion conductor and a second binder; the second stable film layer contains a garnet-structured lithium-ion conductor, a third binder, and a fluorinated lithium salt; wherein, the average particle size of the anti-perovskite-structured lithium-ion conductor is larger than the average particle size of the garnet-structured lithium-ion conductor; the content of the fluorinated lithium salt in the first stable film layer is higher than the content of the fluorinated lithium salt in the second stable film layer.
[0024] In the multilayer composite lithium-ion conductor film, the average particle size of the lithium-ion conductor material exhibits a decreasing gradient distribution, improving the contact performance between the solid electrolyte film and the positive and negative electrodes. The lithium-ion conductors are uniformly distributed within the film, and the interfacial particles of each film layer have good contact, enabling uniform dispersion of all components. This significantly increases the effective contact sites between the multilayer composite lithium-ion conductor film and the positive and negative electrode materials, thereby fully leveraging the interfacial protection and passivation effects provided by the different chemical environments of the components.
[0025] Furthermore, the lithium-ion conductor film contains fluorinated lithium salts with different proportions in the film layers on different electrode sides, which can effectively avoid side reactions between the solvent and the electrolyte or electrode components. This allows for stable matching of high energy density electrodes for charge-discharge cycles, resulting in a significant improvement in the cycle life of solid-state batteries containing this multilayer composite lithium-ion conductor film.
[0026] Furthermore, the presence of a stabilizing film can broaden the electrochemical window of the material and improve humidity stability;
[0027] In summary, the anti-perovskite electrolyte membrane layer of the multilayer composite lithium-ion conductor membrane contains lithium-ion conductors with high ionic conductivity in an anti-perovskite structure. Through the design of different membrane layer chemical compositions and physical particle size distributions, high electrochemical stability for high specific energy positive oxide and negative electrode metallic lithium is achieved, thereby effectively improving the cycle life of solid-state lithium batteries.
[0028] 2. The preparation method provided by this invention is simple, has a short preparation cycle, low cost, and high process controllability, making it suitable for industrial applications. The multilayer composite lithium-ion conductor film obtained also has high versatility. Attached Figure Description
[0029] Figure 1 This is a schematic diagram of the structure of a multilayer composite lithium-ion conductor film according to a specific embodiment of the present invention;
[0030] Figure 2 These are the XRD patterns of the anti-perovskite structure lithium-ion conductors prepared in Preparation Examples 1 and 4 of this invention.
[0031] Figure 3 This is a schematic diagram of the electrochemical cycle performance of solid-state batteries prepared using the lithium-ion conductor films of Example 1 and Comparative Example 1 of the present invention.
[0032] Explanation of reference numerals in the attached figures
[0033] 1. First stabilizing film layer; 2. Anti-perovskite electrolyte film layer; 3. Second stabilizing film layer. Detailed Implementation
[0034] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0035] In this invention, unless otherwise stated, room temperature / normal temperature means 25±2℃.
[0036] In this invention, unless otherwise specified, "first" and "second" do not represent a sequence or limit the various materials or operations, but are merely used to distinguish between them. For example, "first" and "second" in "first stable film layer" and "second stable film layer" are only used to distinguish them and indicate that they are not the same stable film layer.
[0037] As mentioned above, the first aspect of the present invention provides a multilayer composite lithium-ion conductor film, the multilayer composite lithium-ion conductor film comprising a first stabilizing film layer, an anti-perovskite electrolyte film layer and a second stabilizing film layer stacked sequentially.
[0038] The first stable film layer contains a garnet-structured lithium-ion conductor, a first binder, and a fluorine-containing lithium salt;
[0039] The anti-perovskite electrolyte membrane contains an anti-perovskite structure lithium-ion conductor and a second binder.
[0040] The second stabilizing film contains a garnet-structured lithium-ion conductor, a third binder, and a fluorine-containing lithium salt;
[0041] The average particle size of the anti-perovskite lithium-ion conductor is greater than that of the garnet lithium-ion conductor; the content of fluorinated lithium salt in the first stable film layer is higher than that in the second stable film layer.
[0042] like Figure 1 The figure shows a schematic diagram of a multilayer composite lithium-ion conductor film according to a specific embodiment of the present invention. As can be seen from the figure, the multilayer composite lithium-ion conductor film includes a first stabilizing film layer 1, an anti-perovskite electrolyte film layer 2, and a second stabilizing film layer 3, which are sequentially stacked.
[0043] According to some embodiments of the present invention, the multilayer composite lithium-ion conductor film comprises a multilayer film structure stacked sequentially, each film layer independently containing a specific lithium-ion conductor material, and the average particle size of the lithium-ion conductor material in the multilayer composite lithium-ion conductor film exhibits a decreasing gradient distribution. Specifically, the average particle size of the anti-perovskite structure lithium-ion conductor is larger than that of the garnet structure lithium-ion conductor. The various film layer structures cooperate with each other, improving the contact performance between the solid electrolyte membrane and the positive and negative electrodes.
[0044] Furthermore, the films on different electrode sides have different proportions of fluorinated lithium salts. Specifically, the fluorinated lithium salt content in the first stable film layer is higher than that in the second stable film layer. The synergistic structure of each film layer effectively prevents side reactions between the solvent and the electrolyte or electrode components, enabling stable matching with high-energy-density electrodes for charge-discharge cycles. This significantly improves the cycle life of the solid-state battery containing this multilayer composite lithium-ion conductor film.
[0045] The multilayer composite lithium-ion conductor membrane contains an anti-perovskite electrolyte membrane layer with high ionic conductivity. Through the design of different membrane chemical compositions and physical particle size distributions, high electrochemical stability for high specific energy positive oxide and negative metal lithium is achieved, thereby effectively improving the cycle life of solid-state lithium batteries.
[0046] According to some embodiments of the present invention, preferably, the average particle size of the anti-perovskite structure lithium-ion conductors contained in the anti-perovskite electrolyte membrane layer is 0.4-1 μm.
[0047] According to some embodiments of the present invention, preferably, the average particle size of the garnet-structured lithium-ion conductor contained in the first stable film layer is 200-400 nm.
[0048] According to some embodiments of the present invention, preferably, the average particle size of the garnet-structured lithium-ion conductor contained in the second stable film layer is 50-200 nm.
[0049] When the average particle size of the lithium-ion conductor material contained in each film layer meets the above-mentioned range, the contact between the interfacial particles of each film layer is better. This is beneficial to further increase the effective contact sites between the multilayer composite lithium-ion conductor film and the positive and negative electrode materials, and to give full play to the interface protection and passivation effects brought about by the chemical environment of the different components.
[0050] According to some embodiments of the present invention, lithium-ion conductor materials with different average particle sizes are obtained by crushing. Specifically, crushing equipment such as crushers, stirred mills, sand mills, and air jet mills are used to crush the garnet-structured lithium-ion conductors and the anti-perovskite-structured lithium-ion conductors to the above-mentioned target particle size range.
[0051] According to some embodiments of the present invention, preferably, based on the total mass of the first stable film layer, the content of the garnet-structured lithium-ion conductor is 65wt%-89wt%; the content of the first binder is 1wt%-5wt%; and the content of the fluorinated lithium salt is 10wt%-30wt%.
[0052] According to some embodiments of the present invention, preferably, based on the total mass of the anti-perovskite electrolyte membrane layer, the content of the anti-perovskite lithium-ion conductor is 95wt%-99wt%; and the content of the second binder is 1wt%-5wt%.
[0053] According to some embodiments of the present invention, preferably, based on the total mass of the second stable film layer, the content of the garnet-structured lithium-ion conductor is 85wt%-98wt%; the content of the third binder is 1wt%-5wt%; and the content of the fluorinated lithium salt is 1wt%-10wt%.
[0054] By adopting the above preferred embodiment, when the content of each component contained in each film layer meets the above range, it is beneficial to further avoid the occurrence of side reactions between the solvent and the electrolyte or electrode components, and to further stabilize the matching of high energy density electrodes for charge-discharge cycles.
[0055] According to some embodiments of the present invention, preferably, the anti-perovskite lithium-ion conductor has the composition shown in Formula I:
[0056] Li 3-ax M a x O 1-y A y Q formula I;
[0057] Wherein, Q is at least one of F, Cl, Br and I; a is the valence of M, when a = 1, M is at least one of Na, K, Rb and Cs; when a = 2, M is at least one of Mg, Ca, Zn, Sr and Ba; when a = 3, M is at least one of Fe, Al, Ga, In, Sc, Y and La; when a = 4, M is at least one of Ge, Ti, Zr and Hf; when a = 5, M is at least one of V, Nb, Ta and Sb; A is a divalent anion, and is at least one of S, Se and Te; x is 0-1, preferably 0.01-1; y is 0-1, preferably 0.01-1.
[0058] According to some embodiments of the present invention, preferably, the ionic conductivity of the anti-perovskite lithium-ion conductor is 1×10⁻⁶. -3 It exhibits excellent lithium-ion conductivity, ranging from mS / cm to 10mS / cm.
[0059] According to some embodiments of the present invention, by designing cation and anion doping with different ionic radii, the crystal structure of the anti-perovskite lithium-ion conductor can be controlled. This control is achieved by calculating the ratio of cation and anion radii (r) of the crystal structure of the anti-perovskite lithium-ion conductor. - / r + The range of values is used to regulate the crystal structure of the anti-perovskite lithium-ion conductor to be either orthorhombic or cubic. The specific calculation formula is as follows:
[0060] Ratio(r - / r + )={*r Q- +[y]*r A2- +[1-y]*r O2-}÷{[(3-ax) / (3-(a-1)x)]*r Li+ +[x / (3-(a-1)x)]*r Ma+}, where the different r are the radii of each ion.
[0061] The ratio of anion and cation radii Ratio(r) - / r +The range of R is defined as follows: when R∈(0.10,0.18), the crystal structure of the material is orthogonal; when R∈(0.18,0.35), the crystal structure of the material is cubic.
[0062] The anti-perovskite lithium-ion conductor has the composition shown in Formula I. By correcting the tolerance factor for perovskite stability, the ratio of anion and cation radii that regulates the crystal structure of the anti-perovskite lithium-ion conductor, Ratio(r), is obtained. - / r + The range of values for R is defined as follows: when R ∈ (0.13, 0.27), the crystal structure of the anti-perovskite lithium-ion conductor is orthorhombic; when R ∈ (0.27, 0.41), the crystal structure of the anti-perovskite lithium-ion conductor is cubic. Here, R is Ratio(r) - / r + ).
[0063] According to some embodiments of the present invention, preferably, the garnet-structured lithium-ion conductor is LiLaZrO and / or LiLaZrTaO.
[0064] According to some embodiments of the present invention, preferably, the first adhesive, the second adhesive and the third adhesive are each independently selected from at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), (vinylidene fluoride-hexafluoropropylene) copolymer (PVDF-HFP), polyethylene oxide (PEO), polyacrylonitrile (PAN) and styrene-butadiene rubber (SBR).
[0065] According to some embodiments of the present invention, preferably, the average particle size of the first adhesive, the second adhesive and the third adhesive is independently 10-1000 μm.
[0066] According to some embodiments of the present invention, preferably, the number average molecular weight and compression ratio of the first adhesive, the second adhesive and the third adhesive each independently satisfy: number average molecular weight ≥ 100000 g / mol, and compression ratio 1-10000:1.
[0067] By adopting the above preferred embodiments, when the average particle size and / or number-average molecular weight and compression ratio of the first binder, the second binder and the third binder are controlled to meet the above range, the binder can be more easily fiberized under shear force, and the diameter and mechanical strength of the fiber filaments obtained after the binder is fiberized can more easily meet the requirements of ultra-thin electrolyte membranes, and the prepared electrolyte membrane is thinner and more tough.
[0068] According to some embodiments of the present invention, preferably, the anion in the fluorinated lithium salt is bis(trifluoromethanesulfonyl)imide (TFSI). - ), bis(fluorosulfonyl)imide (FSI) - (Fluorosulfonyl)(trifluoromethanesulfonyl)imide ((FSI)(TFSI)) - ), 2-trifluoromethyl-4,5-dicyanimidazolium (TDI) - ), bis(pentafluoroethylsulfonyl)imide (BETI) - ), difluorophosphate (DFP) - ), hexafluorophosphate (PF6) - ), tetrafluoroborate (BF4) - ), hexafluoroarsenate (AsF6) - ), trifluoromethanesulfonate ((SO3CF3) - (TF) - )), fluoroalkyl phosphate ([PF3(CF2CF3)3) - ](FAP - )), tetra(trifluoroacetoxy)borate ([B(OCOCF3)4] - (TFAB - ), difluoro(oxalate)borate ((BF2(C2O4)) - (FOB) - )) and BF2O4R x - At least one of the following; the BF2O4R x - In the middle, R x It is an alkyl group with 1-4 carbon atoms.
[0069] According to some embodiments of the present invention, preferably, the thickness of the multilayer composite lithium-ion conductor film is 10-500 μm, more preferably 10-100 μm, and even more preferably 6-20 μm.
[0070] According to some embodiments of the present invention, preferably, the thickness of the first stabilizing film layer is 1-5 μm.
[0071] According to some embodiments of the present invention, preferably, the thickness of the anti-perovskite electrolyte membrane layer is 4-20 μm.
[0072] According to some embodiments of the present invention, preferably, the thickness of the second stabilizing film layer is 1-5 μm.
[0073] According to some embodiments of the present invention, preferably, the porosity of the multilayer composite lithium-ion conductor film is 1%-25%, more preferably 7%-10%. By adopting the above-mentioned preferred embodiments, the multilayer composite lithium-ion conductor film has the aforementioned specific porosity, which is beneficial for the multilayer composite solid electrolyte film and the solid-state lithium battery made from the film to have superior performance.
[0074] According to some embodiments of the present invention, preferably, the compaction density of the multilayer composite lithium-ion conductor film is 2-6 g / cm³. 3 Preferably 3-5.5 g / cm³ 3 By adopting the preferred embodiment described above, the multilayer composite lithium-ion conductor film has the specific compaction density mentioned above, which is beneficial to enabling the multilayer composite solid electrolyte film and the solid lithium battery made from the film to have superior performance.
[0075] According to some embodiments of the present invention, preferably, the peel strength of the multilayer composite lithium-ion conductor film is 300-800 N / m, more preferably 400-700 N / m. By adopting the above-mentioned preferred embodiments, the multilayer composite lithium-ion conductor film possesses the aforementioned specific peel strength, which is beneficial for the multilayer composite solid electrolyte film and the solid-state lithium battery made from this film to have superior performance.
[0076] According to some embodiments of the present invention, preferably, the ionic conductivity of the multilayer composite lithium-ion conductor film is not less than 0.1 mS / cm, and more preferably 0.5 mS / cm to 5 mS / cm.
[0077] A second aspect of the present invention provides a method for preparing a multilayer composite lithium-ion conductor film as described in the first aspect, the method comprising the following steps:
[0078] (1) A garnet-structured lithium-ion conductor, a first binder and a fluorine-containing lithium salt are mixed and subjected to fiberization treatment to obtain a first stable film precursor;
[0079] (2) The anti-perovskite lithium-ion conductor and the second binder are mixed and subjected to fiberization treatment to obtain an anti-perovskite electrolyte membrane precursor.
[0080] (3) Garnet-structured lithium-ion conductor, third binder and fluorine-containing lithium salt are mixed and subjected to fiberization treatment to obtain second stable film precursor;
[0081] (4) The first stabilizing membrane precursor, the anti-perovskite electrolyte membrane precursor and the second stabilizing membrane precursor are sequentially combined.
[0082] According to some embodiments of the present invention, there is no particular limitation on the order of steps (1), (2), and (3), as long as the first stable membrane precursor, the anti-perovskite electrolyte membrane precursor, and the second stable membrane precursor can be prepared respectively. By preparing different membrane layers in steps, and then in step (4), the different membrane layers are sequentially composited in a specific order to obtain the multilayer composite lithium-ion conductor membrane described in the first aspect of the present invention, wherein the average particle size of the lithium-ion conductor material exhibits a decreasing gradient distribution, and the content of fluorinated lithium salt in the first stable membrane layer is higher than the content of fluorinated lithium salt in the second stable membrane layer.
[0083] According to some embodiments of the present invention, preferably, in step (2), the anti-perovskite lithium-ion conductor is prepared by a method comprising the following steps:
[0084] (a) Under a protective atmosphere, a mixture of lithium hydroxide, lithium oxide, lithium halide and A-containing lithium compounds is melted above the eutectic point to obtain a precursor;
[0085] (b) The mixture containing the precursor and fine metal M powder is heat-treated under a protective atmosphere.
[0086] Using the preferred embodiments described above, the method, through the application of a ternary system of lithium hydroxide, lithium oxide, and lithium halide, can significantly reduce the reaction temperature and shorten the reaction time. Furthermore, the fine powder of metal M, as a chemical substitution source, can effectively promote the dehydrogenation reaction of lithium hydroxide and form chemical doping, increasing lattice defects and significantly improving the lithium-ion conductivity of the anti-perovskite structure lithium-ion conductor.
[0087] According to some embodiments of the present invention, preferably, in step (a), the lithium halide is at least one of lithium fluoride, lithium chloride and lithium bromide.
[0088] According to some embodiments of the present invention, preferably, in step (a), the molar ratio of lithium hydroxide, lithium oxide and lithium halide is 2-2m:m:1, 0 < m < 0.5.
[0089] According to some embodiments of the present invention, preferably, in step (a), the amount of the lithium-containing compound A, calculated as A, satisfies the stoichiometric ratio shown in Formula I. Preferably, the molar ratio of the lithium-containing compound A to the lithium halide, calculated as A, is 0.01-0.5:1.
[0090] According to some embodiments of the present invention, preferably, in step (a), the conditions for the melting treatment include: a temperature of 300-600°C, a holding time of 2-10 h, and a heating rate of 2-10°C / min.
[0091] According to some embodiments of the present invention, preferably, in step (b), the molar ratio of the fine metal M powder (calculated as M) to the lithium halide is 0.05-0.2:1.
[0092] According to some embodiments of the present invention, preferably, in step (b), the conditions of the heat treatment include: a temperature of 400-800°C, a heat treatment time of 10-50 h, and a heating rate of 2-5°C / min.
[0093] According to some embodiments of the present invention, preferably, step (b) further includes cooling the product obtained from the heat treatment to room temperature, and then ball milling it to obtain an anti-perovskite structure lithium-ion conductor that meets the above-mentioned average particle size requirements. Preferably, the cooling rate is 0.5-5°C / min.
[0094] According to some embodiments of the present invention, preferably, in step (4), the composite step includes: sequentially stacking the first stabilizing membrane precursor, the anti-perovskite electrolyte membrane precursor and the second stabilizing membrane precursor, and then performing co-extrusion rolling.
[0095] According to some embodiments of the present invention, preferably, the co-extrusion roll pressing is a whole-body hot pressing, and the hot pressing temperature is 40-100℃.
[0096] According to some embodiments of the present invention, the mixing method is not particularly limited, and conventional equipment in the art can be used for the mixing, such as a mortar and pestle, a grinder, a ball mill, an air jet mill, or a screw extruder. Preferably, the mixing is carried out in a mortar and pestle, where shear force is applied by grinding to fiberize the mixture containing the raw materials, thereby performing the fiberization treatment.
[0097] According to some embodiments of the present invention, there is no particular limitation on the method of overall hot pressing, and conventional equipment in the art can be used to perform the overall hot pressing, such as hot rollers, hot press plates, etc.
[0098] A third aspect of the present invention provides a solid-state lithium battery, the solid-state lithium battery comprising a positive electrode, a negative electrode and a multilayer composite lithium-ion conductor film as described in the first aspect, wherein the positive electrode is located on one side of the first stabilizing film layer and the negative electrode is located on one side of the second stabilizing film layer.
[0099] According to some embodiments of the present invention, the positive electrode is located on one side of the first stabilizing film layer, and the first stabilizing film layer contains a relatively high content of fluorinated lithium salt, resulting in a halogen-rich chemical environment between the film layer and the electrode, which is beneficial to the stability of the interface oxidation potential; the negative electrode is located on one side of the second stabilizing film layer, and the second stabilizing film layer contains a relatively low content of fluorinated lithium salt and a relatively high content of garnet-structured lithium-ion conductors, resulting in an oxide-rich chemical environment between the film layer and the electrode, which is beneficial to the stability of the interface reduction potential; matching the film layers on different electrode sides with fluorinated lithium salts of different proportions can effectively avoid the occurrence of side reactions between the solvent and the electrolyte or electrode components, and can stably match high energy density electrodes for charge-discharge cycles, thereby significantly improving the cycle life of the solid-state battery containing this multilayer composite lithium-ion conductor film.
[0100] According to some embodiments of the present invention, preferably, the current collector of the positive electrode is located on one side of the first stabilizing film layer.
[0101] Preferably, the current collector is aluminum foil, and more preferably a mesh aluminum foil and / or a carbon-coated aluminum foil.
[0102] According to some embodiments of the present invention, preferably, the negative electrode is a lithium-containing negative electrode.
[0103] When the multilayer composite lithium-ion conductor film is applied to a solid-state battery, the thinness of the multilayer composite lithium-ion conductor film and the extremely low content of binder ensure sufficient contact between inorganic electrolyte particles, thus avoiding the influence of binder on the electrolyte lithium-ion conductivity.
[0104] Furthermore, the introduction of a stabilizing film layer enables the multilayer composite lithium-ion conductor film to have good humidity stability, as well as high ion conductivity and a wide electrochemical window, thus enabling solid-state batteries made using the multilayer composite lithium-ion conductor film to achieve better cycle stability.
[0105] According to some embodiments of the present invention, after assembling the multilayer composite lithium-ion conductor film and the lithium metal electrode into a CNT / / solid electrolyte film / / Li mold battery, a linear voltammetric scan is performed. The positive scan peak potential of the multilayer composite solid electrolyte film is ≥4V; the integral current area is ≤5×10 -3 AV / cm 2 Cut-off current density ≤ 0.01 A / cm² 2 For lithium metal, the peak potential is ≤0.5V; the integral current area is ≤1×10⁻⁶. -3 AV / cm 2 Cut-off current density ≤ 0.01 A / cm² 2 .
[0106] According to some embodiments of the present invention, the multilayer composite lithium-ion conductor film is assembled into a lithium symmetric battery, and the battery cycle and critical current density are tested. The battery cycle stability time is ≥800h, the cycle stability lithium insertion / extraction polarization potential is ≤1V, and the critical current density is 0.1-1.1mA / cm². 2 .
[0107] The present invention will be described in detail below through embodiments.
[0108] Unless otherwise specified, all raw materials used in the following preparation examples and embodiments are commercially available products.
[0109] The following preparation examples illustrate the anti-perovskite structure lithium-ion conductor and its preparation method provided by the present invention.
[0110] Preparation Example 1
[0111] (a) Under a protective atmosphere, lithium hydroxide, lithium oxide, lithium halide, and an A-containing lithium compound are mixed and ball-milled, and then the resulting mixture is melt-treated in a vacuum tube furnace to obtain a precursor; wherein:
[0112] The molar ratio of lithium hydroxide, lithium oxide, and lithium halide is 1.8:0.1:1;
[0113] Lithium halides are lithium chloride; lithium sulfides containing lithium A are lithium sulfides.
[0114] The molar ratio of lithium containing A and lithium chloride, calculated as A, is 0.05:1;
[0115] The conditions for the melt treatment were: temperature 300℃, holding time 5h; heating rate 2℃ / min.
[0116] (b) Under a protective atmosphere, the mixture formed by the above precursor and the fine powder of metal M is subjected to heat treatment; wherein:
[0117] The fine powder of metal M is zinc powder;
[0118] The molar ratio of fine metal M powder (calculated as M) to lithium chloride is 0.2:1;
[0119] The heat treatment conditions are: temperature 400℃, heat treatment time 20h; heating rate 2℃ / min.
[0120] (c) After heat treatment, the obtained product was cooled to room temperature at a rate of 5 °C / min, and then ball-milled; the composition of the obtained anti-perovskite lithium-ion conductor was Li 2.6 Zn 0.2 O 0.95 S 0.05 Cl, whose properties are shown in Table 1.
[0121] Preparation Example 2
[0122] The method used in Preparation Example 1 is different, except that:
[0123] In step (a), the molar ratio of lithium containing A (calculated as A) to lithium chloride is 0.1:1;
[0124] In step (b), the fine powder of metal M is magnesium powder;
[0125] The molar ratio of fine metal M powder (calculated as M) to lithium chloride is 0.1:1;
[0126] Everything else is the same; the resulting anti-perovskite lithium-ion conductor has the following composition: Li 2.8 Mg 0.1 O 0.9 S 0.1 Cl, whose properties are shown in Table 1.
[0127] Preparation Example 3
[0128] The method used in Preparation Example 1 is different, except that:
[0129] In step (a), the lithium containing A is lithium selenide;
[0130] In step (b), the fine powder of metal M is iron powder;
[0131] Everything else is the same; the resulting anti-perovskite lithium-ion conductor has the following composition: Li 2.4 Fe 0.2 O 0.95 Se 0.05 Cl, whose properties are shown in Table 1.
[0132] Preparation Example 4
[0133] The preparation method is the same as in Example 1, except that the anti-perovskite lithium-ion conductor was not doped. The specific preparation method is as follows:
[0134] (a) Under a protective atmosphere, lithium hydroxide, lithium oxide, and lithium halide are mixed and ball-milled, and then the resulting mixture is melt-treated in a vacuum tube furnace to obtain a precursor; wherein:
[0135] The molar ratio of lithium hydroxide, lithium oxide, and lithium halide is 1.8:0.1:1;
[0136] Lithium halides are lithium chloride;
[0137] The conditions for the melt treatment were: temperature 300℃, holding time 5h; heating rate 2℃ / min.
[0138] (b) After the melting process, the obtained product is cooled to room temperature at a rate of 5°C / min, and then ball-milled.
[0139] The obtained anti-perovskite lithium-ion conductor has the composition Li3OCl, and its property parameters are shown in Table 1.
[0140] Preparation Example 5
[0141] The method of preparation example 4 is the same, except that in step (a), the lithium halide is lithium bromide;
[0142] Everything else is the same. The composition of the obtained anti-perovskite lithium-ion conductor is Li3OBr, and its property parameters are shown in Table 1.
[0143] Preparation Example 6
[0144] (a) Under a protective atmosphere, lithium hydroxide, lithium oxide, and lithium halide are mixed and ball-milled, and then the resulting mixture is melt-treated in a vacuum tube furnace to obtain a precursor; wherein:
[0145] The molar ratio of lithium hydroxide, lithium oxide, and lithium halide is 1.8:0.1:1;
[0146] Lithium halides are lithium chloride;
[0147] The conditions for the melt treatment were: temperature 300℃, holding time 5h; heating rate 2℃ / min.
[0148] (b) Under a protective atmosphere, the mixture formed by the above precursor and the fine powder of metal M is subjected to heat treatment; wherein:
[0149] The fine powder of metal M is zinc powder;
[0150] The molar ratio of fine metal M powder (calculated as M) to lithium chloride is 0.2:1;
[0151] The heat treatment conditions are: temperature 400℃, heat treatment time 20h; heating rate 2℃ / min.
[0152] (c) After heat treatment, the obtained product was cooled to room temperature at a rate of 5 °C / min, and then ball-milled; the composition of the obtained anti-perovskite lithium-ion conductor was Li 2.6 Zn 0.2 OCl, and its properties are shown in Table 1.
[0153] The anti-perovskite lithium-ion conductors prepared in the preparation examples were subjected to XRD tests, and their anion-to-cation radius ratio (r) was calculated. - / r + The crystal structure was determined, and the results are shown in Table 1.
[0154] The present invention provides, by way of example, XRD patterns of anti-perovskite structure lithium-ion conductors prepared in Preparation Example 1 and Preparation Example 4, as follows: Figure 2 As shown, from Figure 2 The ratio of cation and anion radii in the middle is Ratio(r) - / r + As can be seen, both have a cubic crystal structure.
[0155] The following examples illustrate the multilayer composite lithium-ion conductor film and its preparation method provided by the present invention.
[0156] Example 1
[0157] (i) Garnet-structured lithium-ion conductor, a first binder, and a fluorinated lithium salt are mixed in a mortar and subjected to fibrosis treatment until a dough-like mixture is formed. This mixture is then placed between stainless steel sheets and flattened to obtain a first stable film precursor; wherein:
[0158] Garnet-structured lithium-ion conductors are LLZTO (D50 = 300 nm);
[0159] The first binder is polytetrafluoroethylene (PTFE) (D50 = 100 μm, molecular weight 1,000,000 g / mol, compression ratio 100:1);
[0160] The fluorinated lithium salt is LiTFSI (D50 = 10 μm);
[0161] The mass ratio of garnet-structured lithium-ion conductor, first binder, and fluorine-containing lithium salt is 89:1:10;
[0162] (ii) The anti-perovskite lithium-ion conductor and the second binder are mixed in a mortar and pestle for fibrosis treatment until a dough-like mixture is formed. This mixture is then placed between stainless steel sheets and flattened to obtain the anti-perovskite electrolyte membrane precursor; wherein:
[0163] The anti-perovskite lithium-ion conductor is the anti-perovskite lithium-ion conductor prepared in Preparation Example 1.
[0164] The second binder is PTFE (D50 = 100μm, molecular weight 1,000,000 g / mol, compression ratio 100:1);
[0165] The mass ratio of the anti-perovskite lithium-ion conductor to the second binder is 99:1.
[0166] (iii) Garnet-structured lithium-ion conductor, third binder, and fluorinated lithium salt are mixed in a mortar and subjected to fibrosis treatment until a dough-like mixture is formed. This mixture is then placed between stainless steel sheets and flattened to obtain the second stable film precursor; wherein:
[0167] Garnet-structured lithium-ion conductors are LLZTO (D50 = 200 nm);
[0168] The third binder is PTFE (D50 = 100μm, molecular weight 1,000,000 g / mol, compression ratio 100:1);
[0169] The fluorinated lithium salt is LiTFSI (D50 = 10 μm);
[0170] The mass ratio of garnet-structured lithium-ion conductor, third binder, and fluorine-containing lithium salt is 94:1:5;
[0171] (iv) such as Figure 1 As shown, the first stabilizing membrane precursor, the anti-perovskite electrolyte membrane precursor, and the second stabilizing membrane precursor are sequentially stacked and then repeatedly co-extruded using a hot roll press; wherein:
[0172] The co-extrusion roll pressing is a whole-piece hot pressing process, with a hot pressing temperature of 120℃;
[0173] A multilayer composite lithium-ion conductor film was obtained, and its thickness and the thickness of each layer are shown in Table 2.
[0174] Example 2
[0175] The method is the same as in Example 1, except that:
[0176] In step (i), the garnet-structured lithium-ion conductor is LLZTO (D50 = 400 nm), and all other components are the same, thus obtaining the first stable film precursor;
[0177] In step (ii), the anti-perovskite lithium-ion conductor is the anti-perovskite lithium-ion conductor prepared in Preparation Example 2, and the rest are the same, thus obtaining the anti-perovskite electrolyte membrane precursor.
[0178] In step (iii), the garnet-structured lithium-ion conductor is LLZTO (D50 = 100 nm), and all other components are the same, thus obtaining the precursor for the second stable film;
[0179] In step (iv), the co-extrusion rolling process results in different thicknesses of the multilayer composite lithium-ion conductor film, as shown in Table 2, while the rest are the same.
[0180] Example 3
[0181] The method is the same as in Example 1, except that:
[0182] In step (i), the garnet-structured lithium-ion conductor is LLZO (D50 = 300 nm), and all other components are the same, thus obtaining the first stable film precursor;
[0183] In step (ii), the anti-perovskite lithium-ion conductor is the anti-perovskite lithium-ion conductor prepared in Preparation Example 3, and the rest are the same, thus obtaining the anti-perovskite electrolyte membrane precursor.
[0184] In step (iii), the garnet-structured lithium-ion conductor is LLZO (D50 = 200 nm), and all other components are the same, thus obtaining the precursor for the second stable film;
[0185] Step (iv) involves co-extrusion rolling, which results in different thicknesses of the multilayer composite lithium-ion conductor film, as shown in Table 2. All other steps are the same.
[0186] Example 4
[0187] The method is the same as in Example 1, except that:
[0188] In step (i), the first binder is PVDF; the fluorinated lithium salt is LiTFAB; the mass ratio of garnet-structured lithium-ion conductor, the first binder, and the fluorinated lithium salt is 84:1:15; all other parameters are the same, thus obtaining the first stable film precursor.
[0189] Step (ii) is the same as in Example 1, to obtain the anti-perovskite electrolyte membrane precursor;
[0190] In step (iii), the third binder is PVDF; the fluorinated lithium salt is LiTFAB; the mass ratio of garnet-structured lithium-ion conductor, third binder and fluorinated lithium salt is 91:1:8; all other parameters are the same, and the second stable film precursor is obtained.
[0191] In step (iv), the co-extrusion rolling process results in different thicknesses of the multilayer composite lithium-ion conductor film, as shown in Table 2, while the rest are the same.
[0192] Example 5
[0193] The method is the same as in Example 1, except that:
[0194] In step (i), the first binder is PEO; the fluorinated lithium salt is LiBF2O4R. x (R x (Methyl); the mass ratio of garnet-structured lithium-ion conductor, first binder and fluorine-containing lithium salt is 79:1:20; all other components are the same, to obtain the first stable film precursor;
[0195] Step (ii) is the same as in Example 1, to obtain the anti-perovskite electrolyte membrane precursor;
[0196] In step (iii), the third binder is PEO; the fluorinated lithium salt is LiBF2O4R. x (R x (Methyl); the mass ratio of garnet-structured lithium-ion conductor, third binder and fluorine-containing lithium salt is 89:1:10; all other components are the same, to obtain the second stable film precursor;
[0197] In step (iv), the co-extrusion rolling process results in different thicknesses of the multilayer composite lithium-ion conductor film, as shown in Table 2, while the rest are the same.
[0198] Comparative Example 1
[0199] The method is the same as in Example 1, except that the prepared lithium-ion conductor film is only an anti-perovskite electrolyte film layer (i.e., a single-layer film), and its preparation method is as follows:
[0200] S1. The anti-perovskite lithium-ion conductor and the second binder are mixed in a mortar and pestle for fiberization until a dough-like mixture is formed. This mixture is then placed between stainless steel sheets and flattened to obtain the anti-perovskite electrolyte membrane precursor. Wherein:
[0201] The anti-perovskite lithium-ion conductor is the anti-perovskite lithium-ion conductor prepared in Example 1.
[0202] The second binder is PTFE (D50 = 100μm, molecular weight 1,000,000 g / mol, compression ratio 100:1);
[0203] The mass ratio of the anti-perovskite lithium-ion conductor to the second binder is 99:1.
[0204] S2. The above-mentioned reverse perovskite electrolyte membrane precursor is compacted and repeatedly co-extruded step by step using a hot roller press; wherein, the co-extrusion rolling is a whole hot pressing, and the hot pressing temperature is 120℃.
[0205] A single-layer lithium-ion conductor film (i.e., an anti-perovskite electrolyte film layer) was obtained, and its thickness is shown in Table 2.
[0206] Comparative Example 2
[0207] The method is the same as in Example 1, except that the multilayer composite lithium-ion conductor film prepared does not have a decreasing gradient in lithium-ion conductor particle size. Its preparation method is as follows:
[0208] In step (i), the garnet-structured lithium-ion conductor is LLZTO (D50 = 1 μm), and all other components are the same, thus obtaining the first stable film precursor;
[0209] Step (ii) is the same as in Example 1, to obtain the anti-perovskite electrolyte membrane precursor;
[0210] In step (iii), the garnet-structured lithium-ion conductor is LLZTO (D50 = 1 μm), and all other components are the same, thus obtaining the second stable film precursor;
[0211] In step (iv), the co-extrusion rolling process results in different thicknesses of the multilayer composite lithium-ion conductor film, as shown in Table 2, while the rest are the same.
[0212] Comparative Example 3
[0213] The method is the same as in Example 1, except that the content of fluorinated lithium salt in the first stable film layer is equal to the content of fluorinated lithium salt in the second stable film layer. The preparation method is as follows:
[0214] Step (i) is the same as in Example 1, to obtain the first stable film precursor;
[0215] Step (ii) is the same as in Example 1, to obtain the anti-perovskite electrolyte membrane precursor;
[0216] Step (iii) is the same as step (i), and the second stable membrane precursor is obtained;
[0217] In step (iv), the co-extrusion rolling process results in different thicknesses of the multilayer composite lithium-ion conductor film, as shown in Table 2, while the rest are the same.
[0218] Example 6
[0219] The method is the same as in Example 1, except that the anti-perovskite lithium-ion conductor used is different, and its preparation method is as follows:
[0220] Step (i) is the same as in Example 1, to obtain the first stable film precursor;
[0221] In step (ii), the anti-perovskite lithium-ion conductor is the anti-perovskite lithium-ion conductor prepared in Example 4; the rest are the same as in Example 1, and an anti-perovskite electrolyte membrane precursor is obtained.
[0222] Step (iii) is the same as in Example 1, to obtain the second stable film precursor;
[0223] In step (iv), the co-extrusion rolling process results in different thicknesses of the multilayer composite lithium-ion conductor film, as shown in Table 2, while the rest are the same.
[0224] Example 7
[0225] The method is the same as in Example 1, except that the anti-perovskite lithium-ion conductor used is different, and its preparation method is as follows:
[0226] Step (i) is the same as in Example 1, to obtain the first stable film precursor;
[0227] In step (ii), the anti-perovskite lithium-ion conductor is the anti-perovskite lithium-ion conductor prepared in Example 5; the rest are the same as in Example 1, and an anti-perovskite electrolyte membrane precursor is obtained.
[0228] Step (iii) is the same as in Example 1, to obtain the second stable film precursor;
[0229] In step (iv), the co-extrusion rolling process results in different thicknesses of the multilayer composite lithium-ion conductor film, as shown in Table 2, while the rest are the same.
[0230] Example 8
[0231] The method is the same as in Example 1, except that the anti-perovskite lithium-ion conductor used is different, and its preparation method is as follows:
[0232] Step (i) is the same as in Example 1, to obtain the first stable film precursor;
[0233] In step (ii), the anti-perovskite lithium-ion conductor is the anti-perovskite lithium-ion conductor prepared in Example 6; the rest are the same as in Example 1, and an anti-perovskite electrolyte membrane precursor is obtained.
[0234] Step (iii) is the same as in Example 1, to obtain the second stable film precursor;
[0235] In step (iv), the co-extrusion rolling process results in different thicknesses of the multilayer composite lithium-ion conductor film, as shown in Table 2, while the rest are the same.
[0236] Table 1
[0237]
[0238]
[0239] Note: The crystal structure was obtained through XRD testing.
[0240] Table 2
[0241]
[0242] Test case
[0243] (1) Intrinsic contact properties of multilayer composite lithium-ion conductor films
[0244] To characterize the effect of setting a decreasing particle size gradient distribution between different film layers on the intrinsic physical properties of the multilayer composite lithium-ion conductor film, the porosity, compaction density, and peel strength between the composite solid electrolyte film and the lithium metal electrode sheet of the lithium-ion conductor film prepared in the examples and comparative examples were tested, and the results are shown in Table 3.
[0245] Table 3
[0246] Example 1 7.8 4.3 622 Example 2 7.4 4.1 642 Example 3 8.5 4.5 655 Example 4 8.1 4.3 590 Example 5 8.0 4.2 668 Comparative Example 1 8.9 3.9 498 Comparative Example 2 8.7 3.9 562 Comparative Example 3 9.1 3.8 588 Example 6 8.5 4.2 612 Example 7 8.2 4.1 598 Example 8 8.2 4.2 606
[0247] By comparing the various contact performance indicators, it can be found that Example 1 and Comparative Example 1 both exhibit similar contact performance indicators, indicating that the multilayer film prepared by the present invention is comparable to the single-layer film in terms of particle physical contact, and there is no loss in the overall contact performance of the film due to the increase in the number of film layers.
[0248] By comparing various contact performance indicators, it can be found that compared with Comparative Examples 1-3, Examples 1-8 all exhibit superior contact performance indicators, indicating that the multilayer film prepared by the present invention can achieve better particle solid-phase contact by setting the lithium-ion conductor material with a decreasing gradient distribution of particle size and different proportions of fluorinated lithium salt in the film layers, thereby achieving superior physical properties.
[0249] Compared with Examples 1-5, Examples 6-8 all showed similar contact performance indicators, indicating that the multilayer film prepared by the present invention exhibits good adaptability to anti-perovskite lithium-ion conductors before and after chemical composition modification.
[0250] (2) Electrochemical stability test of lithium metal
[0251] (2-1) Linear voltammetric scan tests were performed on the lithium-ion conductor films obtained in the examples and comparative examples. The CNT / / SSE / / Li mold cells were assembled, and a negative scan from the open circuit voltage to -0.6V was performed with a voltage step of 0.1mV / s.
[0252] (2-2) The lithium-ion conductor films prepared in the examples and comparative examples were subjected to lithium symmetric battery cycle tests and critical current density tests.
[0253] The results are shown in Table 4.
[0254] Table 4
[0255]
[0256] By comparing the peak potential position, curve integral area, cutoff current density, stable cycle time of lithium symmetric battery, lithium insertion / extraction polarization potential and critical current density, the electrochemical stability response of different lithium-ion conductor films to lithium metal can be compared. It was found that the above indicators of the embodiments of the present invention are similar to those of the comparative examples, indicating that the multilayer composite lithium-ion conductor film prepared by the present invention has a particle size gradient and is comparable in stability to lithium metal, and there is no decrease in the overall reduction stability of the film due to the increase of film layers.
[0257] (3) Oxidation stability test
[0258] Linear voltammetric scanning tests were performed on the multilayer composite lithium-ion conductor films prepared in the examples and comparative examples. A CNT / / SSE / / Li mold battery was assembled, and a forward scan from the open circuit voltage to 5V was performed with a voltage step of 0.1mV / s. The results are shown in Table 5.
[0259] Table 5
[0260] unit V <![CDATA[mAV / cm 2 ]]> <![CDATA[mA / cm 2 ]]> Example 1 4.25 0.68 7.05 Example 2 4.25 0.69 5.98 Example 3 4.10 0.70 7.00 Example 4 4.15 0.72 6.23 Example 5 4.15 0.68 6.19 Comparative Example 1 2.55 5.89 10.94 Comparative Example 2 1.85 7.98 12.12 Comparative Example 3 3.75 6.12 12.23 Example 6 4.20 0.70 7.00 Example 7 4.15 0.68 6.78 Example 8 4.05 0.71 6.49
[0261] By comparing the peak potential location, curve integral area, and cutoff current density, the oxidation potential stability response of different multilayer composite films can be compared. It can be found that the above indicators of Examples 1-8 of the present invention are all superior to those of Comparative Examples 1-3. This indicates that the multilayer composite lithium-ion conductor films with different fluorine-containing lithium salt contents prepared by the present invention have a wider electrochemical oxidation window, higher oxidation stability, and better solid-solid contact performance.
[0262] Furthermore, when the average particle size of the lithium-ion conductors in the multilayer composite lithium-ion conductor film has the decreasing gradient distribution of the present invention, the solid electrolyte film has a wider electrochemical oxidation stability window, higher oxidation stability, and better solid-solid contact performance.
[0263] Furthermore, compared with Examples 1-5, Examples 6-8 all exhibited similar oxidative stability performance indicators, indicating that the multilayer film prepared by the present invention shows good adaptability to anti-perovskite lithium-ion conductors before and after chemical composition modification.
[0264] (4) Ion conduction performance test
[0265] The lithium-ion conductor films prepared in the examples and comparative examples were tested for ionic conductivity using the following methods:
[0266] The conductivity of lithium-ion conductive membranes was determined using electrochemical impedance spectroscopy (EIS). Before measurement, a blocked battery was assembled in an argon-filled glove box. Lithium-ion conductive membranes (SSEs) were punched into 10 mm diameter discs and sandwiched between two stainless steel (SS) electrodes, forming a stainless steel / composite solid electrolyte membrane / stainless steel (SS / SSEs / SS) measurement system. EIS was performed using an electrochemical workstation. During the test, the AC perturbation amplitude was set to 5 mV, and the scan frequency range was 100 kHz–7 MHz. The temperature of the measurement system was 25 °C. The test results are shown in Table 6.
[0267] Table 6
[0268] Example 1 1.22 Example 2 0.90 Example 3 1.15 Example 4 0.95 Example 5 1.05 Comparative Example 1 1.20 Comparative Example 2 0.55 Comparative Example 3 0.68 Example 6 0.65 Example 7 0.70 Example 8 0.88
[0269] By comparing Examples 1-8 with Comparative Example 1, all samples showed similar ionic conductivity of not less than 0.5 mS / cm, indicating that the multilayer membranes prepared by the dry method are comparable to the single-layer membranes in terms of ionic conductivity, and there is no excessive reduction in the overall ionic conductivity of the membrane due to the increase of membrane layers or the introduction of fluorine components.
[0270] Compared to Comparative Example 2, Examples 1-8 all exhibited superior lithium-ion conductivity, indicating that the prepared multilayer films, by setting a decreasing particle size gradient distribution of the lithium-ion conductor material, can achieve better particle-solid phase contact, thereby achieving superior lithium-ion conductivity. Multilayer composite films without a particle size gradient exhibit poor contact performance and low ionic conductivity.
[0271] Compared with Comparative Example 3, Examples 1-5 all exhibited superior lithium-ion conductivity, indicating that the prepared multilayer film can avoid significant loss of lithium-ion conductivity by setting an appropriate fluorine ratio. In contrast, composite films with excessively high fluorine ratios have poor interfacial ion transport and low ion conductivity.
[0272] The superior lithium-ion conductivity of Examples 1-5 compared to Examples 6-8 demonstrates that the prepared multilayer film can achieve superior lithium-ion conductivity by incorporating a chemically modified anti-perovskite lithium-ion conductor.
[0273] (5) Solid-state battery testing
[0274] With LiCoO2 as the positive electrode, the loading is 36 mg / cm³. 2 Using lithium metal as the negative electrode, charge-discharge tests were conducted within a voltage range of 2.6-4.2V. The lithium-ion conductor films and lithium sheets prepared in the examples and comparative examples were assembled into batteries, and the cycle performance of solid-state lithium metal batteries was determined.
[0275] This invention provides, by way of example, schematic diagrams of the electrochemical cycling performance of solid-state batteries prepared using the lithium-ion conductor films of Embodiment 1 and Comparative Example 1 of this invention, as shown in the following figures. Figure 3 As shown.
[0276] from Figure 3 As can be seen, the multilayer composite lithium-ion conductor film of Embodiment 1 of the present invention can match the metallic lithium anode at room temperature, and the positive electrode can normally exert its normal specific capacity of 142mAh / g. The battery can stably cycle for more than 80 cycles, demonstrating good cycle stability performance;
[0277] In contrast, the solid-state battery made using the lithium-ion conductor film of Comparative Example 1 exhibited a specific capacity of only 42 mAh / g at the positive electrode, and the battery showed a relatively significant capacity decay.
[0278] By comparing the solid-state battery cycle data of Example 1 with those of Comparative Example 1, it can be seen that the multilayer composite lithium-ion conductor film provided by the present invention has a higher first-cycle discharge specific capacity and superior cycle performance, demonstrating the potential of this multilayer composite film in full-cell applications.
[0279] The results above show that the multilayer composite lithium-ion conductor film provided by the present invention has advantages such as high oxidation stability and high stability against lithium metal reduction.
[0280] Furthermore, the multilayer composite lithium-ion conductor membrane provided by this invention is superior to the unmodified anti-perovskite electrolyte membrane in terms of porosity, compaction density, and ionic conductivity. It can effectively improve the cycle life of all-solid-state lithium batteries and has practical application value.
[0281] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A multilayer composite lithium-ion conductor film, characterized in that, The multilayer composite lithium-ion conductor film includes a first stabilizing film layer, an anti-perovskite electrolyte film layer, and a second stabilizing film layer stacked sequentially. The first stable film layer contains a garnet-structured lithium-ion conductor, a first binder, and a fluorine-containing lithium salt; The anti-perovskite electrolyte membrane contains an anti-perovskite structure lithium-ion conductor and a second binder. The second stabilizing film contains a garnet-structured lithium-ion conductor, a third binder, and a fluorine-containing lithium salt; The average particle size of the anti-perovskite lithium-ion conductor is larger than that of the garnet lithium-ion conductor; the average particle size of the anti-perovskite lithium-ion conductor in the anti-perovskite electrolyte membrane is 0.4-1 μm; the average particle size of the garnet lithium-ion conductor in the first stable membrane is 200-400 nm; and the average particle size of the garnet lithium-ion conductor in the second stable membrane is 50-200 nm. The content of fluorinated lithium salt in the first stabilizing film layer is higher than that in the second stabilizing film layer.
2. The multilayer composite lithium-ion conductor film according to claim 1, wherein, Based on the total mass of the first stable film layer, the content of the garnet-structured lithium-ion conductor is 65wt%-89wt%; the content of the first binder is 1wt%-5wt%; and the content of the fluorinated lithium salt is 10wt%-30wt%.
3. The multilayer composite lithium-ion conductor film according to claim 1, wherein, Based on the total mass of the anti-perovskite electrolyte membrane layer, the content of the anti-perovskite lithium-ion conductor is 95wt%-99wt%; the content of the second binder is 1wt%-5wt%.
4. The multilayer composite lithium-ion conductor film according to claim 1, wherein, Based on the total mass of the second stable film layer, the content of the garnet-structured lithium-ion conductor is 85wt%-98wt%; the content of the third binder is 1wt%-5wt%; and the content of the fluorinated lithium salt is 1wt%-10wt%.
5. The multilayer composite lithium-ion conductor film according to any one of claims 1-4, wherein, The anti-perovskite lithium-ion conductor has the composition shown in Formula I: Li 3-ax M x O 1-y A y Formula I; Wherein, Q is at least one of F, Cl, Br and I; a is the valence of M, when a=1, M is at least one of Na, K, Rb and Cs; when a=2, M is at least one of Mg, Ca, Zn, Sr and Ba; when a=3, M is at least one of Fe, Al, Ga, In, Sc, Y and La; when a=4, M is at least one of Ge, Ti, Zr and Hf; when a=5, M is at least one of V, Nb, Ta and Sb; A is a divalent anion, and is at least one of S, Se and Te; x is 0-1; y is 0-1.
6. The multilayer composite lithium-ion conductor film according to claim 5, wherein, x is 0.01-1; y is 0.01-1.
7. The multilayer composite lithium-ion conductor film according to any one of claims 1-4, wherein, The ionic conductivity of the anti-perovskite lithium-ion conductor is 1×10⁻⁶. -3 mS / cm to 10 mS / cm.
8. The multilayer composite lithium-ion conductor film according to any one of claims 1-4, wherein, The garnet-structured lithium-ion conductor is LiLaZrO and / or LiLaZrTaO.
9. The multilayer composite lithium-ion conductor film according to any one of claims 1-4, wherein, The first adhesive, the second adhesive, and the third adhesive are each independently selected from polyvinylidene fluoride, polytetrafluoroethylene, and polyvinylidene fluoride. At least one of hexafluoropropylene copolymer, polyethylene oxide, polyacrylonitrile and styrene-butadiene rubber.
10. The multilayer composite lithium-ion conductor film according to any one of claims 1-4, wherein, The average particle size of the first adhesive, the second adhesive, and the third adhesive is independently 10-1000 μm.
11. The multilayer composite lithium-ion conductor film according to any one of claims 1-4, wherein, The number-average molecular weight and compression ratio of the first adhesive, the second adhesive and the third adhesive each independently satisfy the following: number-average molecular weight ≥ 100000 g / mol, compression ratio 1-10000:
1.
12. The multilayer composite lithium-ion conductor film according to any one of claims 1-4, wherein, The anion in the fluorinated lithium salt is TFSI. - FSI - (FSI)(TFSI) - TDI - BETI - DFP - PF6 - BF4 - AsF6 - (SO3CF3) - (TF) - ), [PF3(CF2CF3)3 - ](FAP - [B(OCOCF3)4] - (TFAB - (BF2(C2O4)) - (FOB) - ) and BF2O4R x - At least one of them, wherein R x It is an alkyl group with 1-4 carbon atoms.
13. The multilayer composite lithium-ion conductor film according to any one of claims 1-4, wherein, The thickness of the multilayer composite lithium-ion conductor film is 10-500 μm.
14. The multilayer composite lithium-ion conductor film according to any one of claims 1-4, wherein, The thickness of the first stabilizing film is 1-5 μm.
15. The multilayer composite lithium-ion conductor film according to any one of claims 1-4, wherein, The thickness of the anti-perovskite electrolyte membrane is 4-20 μm.
16. The multilayer composite lithium-ion conductor film according to any one of claims 1-4, wherein, The thickness of the second stabilizing film is 1-5 μm.
17. The multilayer composite lithium-ion conductor film according to any one of claims 1-4, wherein, The porosity of the multilayer composite lithium-ion conductor film is 1%-25%.
18. The multilayer composite lithium-ion conductor film according to any one of claims 1-4, wherein, The compaction density of the multilayer composite lithium-ion conductor film is 2. 6g / cm 3 .
19. The multilayer composite lithium-ion conductor film according to any one of claims 1-4, wherein, The peel strength of the multilayer composite lithium-ion conductor film is 300. 800 N / m.
20. The multilayer composite lithium-ion conductor film according to any one of claims 1-4, wherein, The ionic conductivity of the multilayer composite lithium-ion conductor film is not less than 0.1 mS / cm.
21. A method for preparing a multilayer composite lithium-ion conductor film as described in any one of claims 1-20, characterized in that, The preparation method includes the following steps: (1) A garnet-structured lithium-ion conductor, a first binder, and a fluorinated lithium salt are mixed and subjected to a fiberization process to obtain a first stable film precursor; (2) The anti-perovskite lithium-ion conductor and the second binder are mixed and subjected to fiberization treatment to obtain the anti-perovskite electrolyte membrane precursor; (3) Garnet-structured lithium-ion conductor, third binder and fluorine-containing lithium salt are mixed and subjected to fiberization treatment to obtain second stable film precursor; (4) The first stabilizing membrane precursor, the anti-perovskite electrolyte membrane precursor and the second stabilizing membrane precursor are sequentially combined.
22. The preparation method according to claim 21, wherein, In step (2), the anti-perovskite lithium-ion conductor is prepared by a method comprising the following steps: (a) Under a protective atmosphere, a mixture of lithium hydroxide, lithium oxide, lithium halide and A-containing lithium compounds is melted above its eutectic point to obtain a precursor; (b) The mixture containing the precursor and fine metal M powder is heat-treated under a protective atmosphere.
23. The preparation method according to claim 22, wherein, In step (a), the molar ratio of lithium hydroxide, lithium oxide and lithium halide is 2-2m:m:1, 0 < m < 0.
5.
24. The preparation method according to claim 22, wherein, In step (a), the conditions for the melting treatment include: a temperature of 300-600℃, a holding time of 2-10h, and a heating rate of 2-10℃ / min.
25. The preparation method according to claim 22, wherein, In step (b), the molar ratio of the fine metal M powder (calculated as M) to the lithium halide is 0.05-0.2:
1.
26. The preparation method according to claim 22, wherein, In step (b), the heat treatment conditions include: a temperature of 400-800℃, a heat treatment time of 10-50h, and a heating rate of 2-5℃ / min.
27. The preparation method according to any one of claims 21-26, wherein, In step (4), the composite step includes: stacking the first stabilizing membrane precursor, the anti-perovskite electrolyte membrane precursor and the second stabilizing membrane precursor in sequence, and then performing co-extrusion rolling.
28. The preparation method according to claim 27, wherein, The co-extrusion roll pressing is a whole-body hot pressing, and the hot pressing temperature is 40-100℃.
29. A solid-state lithium battery, characterized in that, The solid-state lithium battery includes a positive electrode, a negative electrode, and a multilayer composite lithium-ion conductor film as described in any one of claims 1-20, wherein the positive electrode is located on one side of the first stabilizing film layer, and the negative electrode is located on one side of the second stabilizing film layer.
Citation Information
Patent Citations
Solid-state electrolyte, solid-state battery and preparation method thereof
CN114759252A